Редокс-стан тромбоцитів у хворих на рак прямої кишки та його вплив на ефективність лікування - Бурлака, А.П.; Голотюк, В.В.; Вовк, А.В.; Лукін, С.М.; Сидорик, Є.П. (Онкологія, 2015)
Platelets play an important role in the processes that are associated with tumor growth, metastasis, neoangiogenesis, tumor-associated thrombosis. Stimulation of the platelets initiates the generation of superoxide radicals and nitric oxide NO, which in turn contributes to the progression of malignant tumors, including rectal cancer (RC). Objective: to investigate the redox state of platelets at different stages of treatment of patients with RC and the relationship between platelet activity and overall survival of patients (control). Subjects and methods: platelets of 48 patients with RC (T2–4N0–2M0G2) and 15 donors (control group) were studied. The investigation of superoxid- and NO-generating activity of platelets was performed by electron paramagnetic resonance technology with spin trap. Survival was analyzed by Kaplan — Meier method using χ2 and log-rank criteria. Results: in patients with RC were revealed high activity of NADP•H-oxidase platelets, which is 8–14 times higher than the reference value, and at the same time the low activity of inducible NO-synthase (iNOS), which was 2.6– 5.6 times lower than the performance of donors. After neoadjuvant radiotherapy and tumor removal were registered decreased activity of NADP•Hoxidase and increasing — iNOS, but physiological limits were not reached. 5-year overall survival of patients who at 1 month after surgery it was found the greatest reduction activity of NADP•H-oxidase (< 1.5 nM/10⁵ cell·min, lower than the median index at this time of investigation) was significantly (p < 0.004) better than that in patients with higher levels of generation of superoxide radicals. Conclusion: determination of the dynamics of activity of NADP•H-oxidase on the stages of treatment of the RC (especially the degree of reduction after surgery) may be an additional criterion for prediction of treatment effectiveness. Тромбоцити відіграють важливу роль у процесах, пов’язаних із ростом
пухлини, метастазуванням, неоангіогенезом, пухлиноасоційованим тромбозом. Стимуляція тромбоцитів ініціює генерування супероксидних радикалів та оксиду азоту (NO), що, в свою чергу, сприяє прогресуванню злоякісних пухлин, у тому числі раку прямої кишки (РПК). Мета: дослідити редокс-стан тромбоцитів на різних етапах лікування хворих на РПК
і зв’язок між активністю тромбоцитів і загальною виживаністю пацієнтів. Об’єкт і методи: досліджено тромбоцити 48 хворих на РПК (Т2–
4N0–2M0G2) та 15 донорів (контроль). Визначення супероксид- та NOгенеруючої активності тромбоцитів проводили методом електронного парамагнітного резонансу з використанням технології спінових уловлювачів.
Виживаність аналізували за методом Каплана — Мейєра, використовуючи χ2
та log-rank критерії. Результати: у хворих на РПК виявлено високу активність НАДФ•Н-оксидази тромбоцитів, яка у 8–14 разів перевищує контрольні значення, і водночас низьку активність індуцибельної
NO-синтази (iNOS), яка у 2,6–5,6 раза нижча за показники у донорів.
Після неоад’ювантної променевої терапії та видалення пухлини зареєстровано зниження активності НАДФ•Н-оксидази та підвищення
iNOS, однак фізіологічних меж вони не досягли. 5-річна загальна виживаність хворих, у яких через 1 міс після операції встановлено найбільше зниження активності НАДФ•Н-оксидази (< 1,5 нМ/10⁵ клітин·хв,
що нижче за медіану показника на цей термін обстеження), була достовірно (p < 0,004) кращою, ніж пацієнтів із більш високими рівнями
генерації супероксидних радикалів. Висновок: визначення динаміки активності НАДФ•Н-оксидази на етапах лікування хворих на РПК (особливо ступеня зниження після операції) може бути додатковим критерієм прогнозу ефективності лікування.